Treatment of Obesity with Thyroid hormones in Europe. Data from the THESIS* Collaboration - Galofré, J C; Díez, J J; Attanasio, R; Nagy, E V; Negro, R; Papini, E; Perros, P; Žarković, M; Akarsu, E; Alevizaki, M; Ayvaz, G; Bednarczuk, T; et al. (Journal of endocrinological investigation, 2025)
PURPOSE: The use of thyroid hormones (TH) to treat obesity is unsupported by evidence as reflected in international guidelines. We explored views about this practice, and associations with respondent characteristics among European thyroid specialists. METHODS: Specialists from 28 countries were invited to a survey via professional organisations. The relevant question was whether "Thyroid hormones may be indicated in biochemically euthyroid patients with obesity resistant to lifestyle interventions". RESULTS: Of 17,232 invitations 5695 responses were received (33% valid response rate; 65% women; 90% endocrinologists). Of these, 290 (5.1%) stated that TH may be indicated as treatment for obesity in euthyroid patients. This view was commoner among non-endocrinologists (8.7% vs. 4.7%, p < 0.01), private practice (6.5% vs. 4.5%, p < 0.01), and varied geographically (Eastern Europe, 7.3%; Southern Europe, 4.8%; Western Europe, 2.7%; and Northern Europe, 2.5%). Respondents from Northern and Western Europe were less likely to use TH than those from Eastern Europe (p < 0.01). Gross national income (GNI) correlated inversely with this view (OR 0.97, CI: 0.96-0.97; p < 0.001). Having national guidelines on hypothyroidism correlated negatively with treating obesity with TH (OR 0.71, CI: 0.55-0.91). CONCLUSIONS: Despite the lack of evidence, and contrary to guidelines' recommendations, about 5% of respondents stated that TH may be indicated as a treatment for obesity in euthyroid patients resistant to life-style interventions. This opinion was associated with (i) respondent characteristics: being non-endocrinologist, working in private practice, treating a small number of hypothyroid patients annually and (ii) national characteristics: prevalence of obesity, Eastern Europe, low GNI and lack of national hypothyroidism guidelines.
Keywords: dospělí; Levothyroxine; lékařská praxe - způsoby provádění; průzkumy a dotazníky; Europe; Female; Adult; ženské pohlaví; Surveys and Questionnaires; Obesity; lidé; Evropa; Survey; Hypothyroidism; obezita; Male; Thyroid Hormones; hormony štítné žlázy; lidé středního věku; mužské pohlaví; Middle Aged; Practice Patterns, Physicians'; Humans